Dampak Kemampuan Menggunakan Teknologi Digital terhadap Motivasi Belajar dan Kreativitas Siswa dalam Pembelajaran Pendidikan Agama Islam - Dahliah; Wahab (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the effect of digital technology proficiency on students’ learning motivation and creativity in Islamic Religious Education (PAI). A quantitative approach was employed using a survey method involving 111 respondents. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that digital technology proficiency has a positive and significant influence on both learning motivation and students’ creativity. Measurement model evaluation indicates high internal consistency, with Cronbach’s Alpha values exceeding 0.90, and satisfactory convergent validity, as reflected by Average Variance Extracted (AVE) values above 0.67 for all constructs. These findings highlight that the effective integration of digital technology in PAI learning enhances students’ engagement and supports the development of creative thinking in understanding and applying Islamic values. This study implies that teachers should strategically optimize digital technology integration to create more interactive, contextual, and student-centered learning environments aligned with contemporary educational demands